THE EFFECT OF "ARGUMENT-BASED SCIENCE INQUIRY" APPROACH ON SCIENCE TEACHER CANDIDATES' ACADEMIC ACHIEVEMENTS - Cigdem Guler; Mustafa Dogru (Informascope, 2017)
Science education, when it is dealt with in terms of subject, activities and target behaviours, is an open area to inquiry and development. However, this case is interpreted from a different point of view in a lot of educational institutions in our country (Turkey). The aim of this study is to evaluate the effect of "Argument-Based Science Inquiry (ABSI)" approach on the academic achievements of 3rd grade Science Education teacher candidates by applying this approach to the activities and establishing a suitable educational environment, and to reveal their thoughts about it. Mixed methods research has been used in this paper. In the quantitative dimension of the research, a pre-test post-test control group experimental design has been used. At the end of the implementation process, an achievement test has been applied to both groups, and results have been analyzed statistically. The results have shown that there is a statistically significant difference between the pre-test and post-test results of experimental group, and ABSI approach has a positive effect on student success. In the qualitative dimension of the study, semi-structured interviews have been used with the experimental group's teacher candidates. Data have been analyzed through content analysis method. In accordance with all findings, it is deduced that the ABSI activities affect the academic achievement of teacher candidates more positively than the classical laboratory practices in Laboratory Practices II class.